2022
DOI: 10.1177/09564624221086255
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of the QuickStripe™ chlamydia rapid test among high-risk women in Jakarta

Abstract: Background Difficulty in diagnosing Chlamydia trachomatis infections, including chlamydial cervicitis, is a notable challenge in managing sexually transmitted infections in Indonesia. Gram staining is usually done to make a presumptive diagnosis despite its low sensitivity and specificity. Polymerase chain reaction (PCR) is considered the gold standard, but it is costly, technically demanding, and difficult to be performed in low-resource settings. Thus, rapid point-of-care tests with high sensitivity and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…As one of the available rapid antigen tests for Chlamydia infection, the QuickStripe™ Chlamydia Ag (Savyon Diagnostics Ltd., Ashdod, Israel), a rapid chromatographic immunoassay for the qualitative detection of Chlamydia trachomatis in the female cervical swab, male urethral swab, and male urine specimens [ 88 ] was reported to be effective, particularly in a high-risk population. With a turnaround time of 10 min, the QuickStripe™ Chlamydia Ag demonstrated a sensitivity of 73.6% and specificity of 81.82%, with positive and negative predictive values of 77.78% and 78.05%, respectively [ 89 ]. A systematic review on the clinical performance of RATs for Chlamydia infection, however, reported a pooled sensitivity of 53%, 37%, and 63% for cervical swabs, vaginal swabs, and male urine, respectively, although the specificity was considered high (99%, 97%, and 98%, respectively) [ 90 ].…”
Section: Rats As a Detection Tool To Aid The Clinical Diagnosis Of Ot...mentioning
confidence: 99%
“…As one of the available rapid antigen tests for Chlamydia infection, the QuickStripe™ Chlamydia Ag (Savyon Diagnostics Ltd., Ashdod, Israel), a rapid chromatographic immunoassay for the qualitative detection of Chlamydia trachomatis in the female cervical swab, male urethral swab, and male urine specimens [ 88 ] was reported to be effective, particularly in a high-risk population. With a turnaround time of 10 min, the QuickStripe™ Chlamydia Ag demonstrated a sensitivity of 73.6% and specificity of 81.82%, with positive and negative predictive values of 77.78% and 78.05%, respectively [ 89 ]. A systematic review on the clinical performance of RATs for Chlamydia infection, however, reported a pooled sensitivity of 53%, 37%, and 63% for cervical swabs, vaginal swabs, and male urine, respectively, although the specificity was considered high (99%, 97%, and 98%, respectively) [ 90 ].…”
Section: Rats As a Detection Tool To Aid The Clinical Diagnosis Of Ot...mentioning
confidence: 99%